2022
DOI: 10.1111/eci.13809
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for stratifying patients with lifelong premature ejaculation before using the PHQ‐9: An observational study

Abstract: Objective A PHQ‐9 score ≥ 15, represented as PHQ‐9+, indicates major depressive disorder (MDD). On using PHQ‐9, the psychological burden of several patients with lifelong premature ejaculation (LPE) gets aggravated, which may lead to LPE development. We aim to construct a nomogram for predicting the individual risk of PHQ‐9+ in patients with LPE and discerning those with low risks, who should avoid the PHQ‐9. Methods The nomogram was constructed by analysing data of 802 patients from Xijing Hospital and Northw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“… 4 Male sexual function can be assessed by several psychometric scales: the 6-item International Index for Erectile Function (IIEF-6), the Erection Hardness Scale (EHS), and the Masturbation Erection Index (MEI) can be used to assess aspects related to erectile function; moreover, the Premature Ejaculation Diagnostic Tool (PEDT) can be used to assess the presence of premature ejaculation (PE) and its clinical consequences. 5 6 7 8 9 10 Several studies have confirmed the diagnostic accuracy of the EHS and IIEF-6. 11 12 13 14 15 The MEI is an adaptation of the IIEF-6 that is applied to masturbation; this scale is particularly useful for erectile dysfunction (ED) patients who have not engaged in penetrative sexual intercourse in the past 4 weeks.…”
Section: Introductionmentioning
confidence: 91%
“… 4 Male sexual function can be assessed by several psychometric scales: the 6-item International Index for Erectile Function (IIEF-6), the Erection Hardness Scale (EHS), and the Masturbation Erection Index (MEI) can be used to assess aspects related to erectile function; moreover, the Premature Ejaculation Diagnostic Tool (PEDT) can be used to assess the presence of premature ejaculation (PE) and its clinical consequences. 5 6 7 8 9 10 Several studies have confirmed the diagnostic accuracy of the EHS and IIEF-6. 11 12 13 14 15 The MEI is an adaptation of the IIEF-6 that is applied to masturbation; this scale is particularly useful for erectile dysfunction (ED) patients who have not engaged in penetrative sexual intercourse in the past 4 weeks.…”
Section: Introductionmentioning
confidence: 91%